Daniel X. 1 - Patterson, James, 1947-; Ledwidge, Michael (Yen Press, 2010)
After his parents are murdered by an intergalactic criminal, Daniel X assumes his father's role an an Alien Hunter and hopes that his gift of being able to create anything he can imagine will be enough to overcome the sixth-deadliest criminal on his list.